2022
DOI: 10.3390/su14074020
|View full text |Cite
|
Sign up to set email alerts
|

ELM-Based Non-Singular Fast Terminal Sliding Mode Control Strategy for Vehicle Platoon

Abstract: Vehicle platoon is one of the innovations in the automated highway systems, which has the potential to reduce fuel consumption, alleviate traffic congestion and lighten the driver’s burden. How to control the vehicle effectively to ensure the stability of the queue is a challenge. Aiming to overcome the shortcomings of the platoon control method based on traditional sliding mode control, a non-singular terminal sliding mode control method optimized by the extreme learning machine is proposed in this paper. Fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 44 publications
(60 reference statements)
0
1
0
Order By: Relevance
“…Jin et al (2018) suggested a new fluid queuing model that described the macroscopic effect of platooning operations on highway congestion. Wang and Du (2022) identified that vehicle platoons can contribute to innovations in automated highway systems, which would further reduce the burden on the highway system. Beaver and Malikopoulos (2021) used highway platooning as a case study to integrate constraint-driven optimal control of multiagent systems.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Jin et al (2018) suggested a new fluid queuing model that described the macroscopic effect of platooning operations on highway congestion. Wang and Du (2022) identified that vehicle platoons can contribute to innovations in automated highway systems, which would further reduce the burden on the highway system. Beaver and Malikopoulos (2021) used highway platooning as a case study to integrate constraint-driven optimal control of multiagent systems.…”
Section: Literature Reviewmentioning
confidence: 99%